Towards the first radio galaxies. Issue Volume 15:Issue S352(2019) (June 2019) - Matute, Israel; Afonso, Jose; Bizzocchi, Luca; Pappalardo, Cirino; Messias, Hugo; Amarantidis, Stergios
Abstract: Powerful AGN have been detected up to very high redshifts (z ∼ 6–8), well within the Epoch of Reionization (EoR), but the lack of powerful radio-galaxies among such sources strongly disagrees with the expectations based on the known radio population up to z ∼ 5. Our group has been pursuing a detailed analysis of the faintest population of radio sources detected in the deepest fields searching for clues of these first radio galaxies. This paper describes our strategy and presents a highly confident candidate. The results, once follow-up of all candidates is completed, will have significant implications for the upcoming generation of all-sky deep radio surveys such as ASKAP-EMU, Westerbork-WODAN, and SKA itself.